EFFORT TO IMPROVE UNDERSTANDING OF FIQH REGARING THE PILLARS OF FAITH TROUGH THE DISCOVERY LEARNING METHOD - Rahmati; Suprizal (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
his study aims to examine efforts to improve the understanding of Fiqh regarding the Pillars of Faith through the Discovery Learning method in Grade II of SD Negeri 2 Jangka Buya. The research method used is Classroom Action Research (CAR) with a qualitative approach. The subjects of this study were 30 second-grade students. Data collection was conducted through observations, written tests, and interviews. The results showed that the application of the Discovery Learning method effectively improved students' understanding of the Pillars of Faith. Based on the findings, there was an increase in student engagement from Cycle I to Cycle II, with students becoming more active and enthusiastic in learning. It can be concluded that the Discovery Learning method is effective in enhancing students' understanding of the Pillars of Faith, making the learning process more engaging and interactive. Therefore, it is recommended that this method be consistently applied in Fiqh learning at the elementary school level.